MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP BILANGAN ANAK USIA DINI KELOMPOK B MELALUI METODE OPEN ENDED - Rohmalina, rohmalina; Komala, Komala (IKIP Siliwangi, 2020)
In this study the researcher concluded the results of the two groups studied, namely the experimental group and the control group. In the experimental class the researchers gave treatments using the open-ended method, while for the control group the researchers provided treatments using ordinary learning using children's worksheets (LKA). The study began with conducting a pretest and posttest in both groups. The results of this study are that the open-ended method can develop children's abilities in recognizing the concept of numbers (Rohmalina et al., 2021). Based on the results of the independent t-test, the posttest data shows that the p value is 0.01. And 0.01 <0.05 so that Ho is rejected and Ha is accepted, thus the posttest results (after the treatment) are stated to have increased after the treatment was carried out using the open-ended method.Â